Prevención de enfermedades respiratorias en adultos de 20 - 50 Años de la Comunidad Urbina. - Enríquez Jiménez, Evelyn Eliana (2024)
Respiratory diseases are disorders that affect the organs and tissues that make breathing possible, becoming a problem for health institutions, for this reason the objective of this research was to develop an educational plan for the prevention of respiratory diseases in adults aged 20 to 50 years in the Urbina community. For this purpose, it was necessary to use a methodology based on the quantitative approach, supported by types of research such as bibliographic, field or action, to which theoretical methods such as historical-logical, synthetic analytical and inductivedeductive were added, which supported the instrument that was the questionnaire and that was applied to the study population. Among its main results, 52% of respondents admitted not having received information on the prevention of respiratory diseases, reflecting a notable deficiency in education and available resources. In addition, the preference of 60% was to go to pharmacies instead of medical services suggests insufficient access to professional health care or a lack of awareness of its importance. This panorama is further complicated by 31% of individuals recently diagnosed with a respiratory disease, highlighting a probable exposure to risk factors without adequate preventive interventions. Thus, an educational plan was developed focused on behavioral change and the adoption of healthy practices such as regular hygiene and timely consultation with health professionals